Faktor Penyebab Kesulitan Mengenali Huruf Pada Siswa Kelas Rendah (Studi Kasus Di Sdx Tanah Datar). : kesulitan mengenali huruf pada anak sekolah dasar kelas rendah - mardina hafizah (Tadzkirah : Jurnal Pendidikan Dasar, 2023)
This phenomenon is motivated by the large number of students who have difficulty recognizing letters which results in being unable to read or carry out activities that support the development of knowledge, and the purpose of this research is to describe the problems that researchers find in the field which focuses research on the causes of students' difficulties in recognizing letters, and researchers use a qualitative research methodology that describes the findings that researchers get during research in the field. The results that researchers get include, such as lack of focus during learning takes place, confused with the shape of the letters, and likes to rely on other people. However, what the researchers found that stood out was the high use of the lecture method, the average student having high kinesthetic abilities, and a lack of confidence in the students themselves.